Enhancing Indonesian Language Skills through Cooperative Learning: Implementing the Jigsaw Method at MIS Nurul Falah Cihuni - Neneng Mu'afakoh; Yuliana Kawitania Dewi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to explore the effectiveness of the Jigsaw cooperative learning method in enhancing Indonesian language skills at MIS Nurul Falah Cihuni. Cooperative learning has proven to be a beneficial teaching strategy, promoting active student participation, collaboration, and deeper understanding of the material. The Jigsaw method, in particular, encourages students to work in small, diverse groups, each responsible for learning and teaching a specific segment of the lesson. This research investigates how the Jigsaw method can improve the students' Indonesian language proficiency, focusing on their reading, writing, listening, and speaking skills. The research was conducted in a classroom setting at MIS Nurul Falah Cihuni, with a sample of students from grades 4 and 5. Data were collected through a combination of pre- and post-assessments, classroom observations, and interviews with both students and teachers. The pre-assessment evaluated the students' initial language proficiency, while the post-assessment measured their progress after the implementation of the Jigsaw method. Classroom observations provided insight into student engagement, collaboration, and participation, while interviews helped to gather feedback on the students' learning experiences. The results of the study indicate that the Jigsaw method significantly improved the students' Indonesian language skills. Students showed higher engagement, better collaboration, and an increased understanding of the language concepts taught. The method also fostered a more supportive learning environment, where students felt encouraged to share knowledge and learn from one another. This study highlights the potential of cooperative learning, particularly the Jigsaw method, in enhancing language acquisition and promoting a more interactive, student-centered approach to learning.